Factors Affecting Banking Fraud Prevention and Their Impact On The Quality of Financial Statements - Metha Christinawati; Hari Setiyawati (Universitas Pendidikan Ganesha, 2022)
This research begins with a phenomenon where several banking sector companies experience increased corruption cases in financial management. The low internal control system and the lack of good corporate governance are opportunities to commit fraud by taking advantage of positions and positions. If these two things are done well, the company can undoubtedly minimize fraud, which will affect the quality of its financial statements. This study aims to analyze the role of banks in practicing reasonable internal control and governance systems. This research uses a quantitative approach with a causal type of research. This research uses a quantitative approach with a causal type of research. The population in this study is a national private commercial bank listed on the Indonesia Stock Exchange. The sample was determined based on the accidental method, with a total sample of 34 established bank companies. The process of collecting primary data using a questionnaire. Data were analyzed and processed using Smart PLS. The results showed that the internal control system had a positive and significant effect on fraud prevention but no effect on financial reports' quality. At the same time, the principles of good corporate governance have a positive and significant effect on fraud prevention and the quality of financial reports. Fraud prevention has a positive and significant effect on the quality of financial reports.